A MODEL INTEGRATING CULTURAL DIVERSITY EDUCATION INTO THE ACCOUNTING CURRICULUM IN HIGHER INSTITUTION - Muslichah Muslichah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
Education is one of the elements of character formation and development of human beings. Cultural diversity education is a conscious effort to develop personality inside and outside school to learn about the different kinds of social status, race, ethnicity, religion in order to create a good personality in dealing with issues of cultural diversity. In this article we propose a framework of cultural diversity education in academic program for accounting students. The education emphasizes knowledge of and interaction with other cultures and ethnicities.Cultural diversity education and understanding of the relativity of cultural differences is a our growing sense and awareness of the importance of respect, recognize and accept the diversity that already exist